Aller-retour-détour: Transdiasporic Nomadism and the Navigation of Literary Prescription in the Work of Kim Thúy and Thanh-Van Tran-Nhut. Issue 1 (April 2018) - Kurmann, Alexandra
Abstract : In Ru and Le Palais du Mandarin Kim Thúy and Thanh-Van Tran-Nhut respectively depict multiple homecomings and lateral mobility across the diaspora, signalling a transition in Vietnamese-Francophone Studies from an engagement with exile-writing to the production of a transdiasporic literature. Such a turn involves writing for the transnational Việt Kiều community as much as for readers across nations of settlement. Correspondingly, Thúy recounts her family's flight and her aller-retours to Vietnam, while expressing gratitude towards her North American readership, while Tran-Nhut's culinary travel stories whet the appetite of a Franco-French public at the same time as satiating the nostalgic desires of Vietnamese-Francophone readers. Yet both writers simultaneously resist such prescription of their work in Glissantian narrative detours that circumvent readerly claims on the text. A new transdiasporic nomadism offered here, which encompasses literary navigations across, within, and beyond the borders of the Vietnamese diaspora, facilitates literary resistance by providing a shared elsewhere whence to write.